Peningkatan Keterlibatan Dalam Perkuliahan Scientific Writing Menggunakan Model Pengajaran Social Inquiry - Suwartono Suwartono; Santhy Hawanti (Universitas Negeri Malang, 2016)
This research aimed to solve student low involvement in Scientific Writing classes.The method used in this research was Classroom Action Research (CAR). The planned action was Social Inquiry teaching model, i.e. an autonomous instruction in which students do inquiries for facts (new knowledge on scientific writings along with the linguistic aspects of writings) and exercises in communicating the inquiry results within the classroom society are prioritized. The CAR employed Lewin's cyclic model. The model procedures are: (1) identification, evaluation and formulation of the problem; (2) fact finding; (3) review of literature; (4) information gathering to test hypothesis; (5) selection of the planned action procedures; (6) implementation; and (7) interpretation of the data and overall evaluation. The CAR's result has shown that teaching Scientific Writing using Social Inquiry can promote student involvement in scientific writing class activities.